O internato como modelo educacional segundo a literatura: um estudo sob a perspectiva da teoria crítica - Santana, Jeová Silva (2011)
The study analyzed the works of Brazilian literature that have the boarding school model as its theme. It was intended to determine whether these specific forms of construction fulfilled only the aesthetic motivations of its authors, or could serve as sources of research to meet certain educational practices of the Brazilian educational process. To that end, he established himself as the chronological cut late nineteenth century and the 1920s, and was chosen by the authors that started boarding school and later recreated that experience school through several genres: romance, memorialism, lyrical. From this perspective, constituted the corpus with the works O Ateneu, by Raul Pompeia; Doidinho, by José Lins do Rego; As Três Marias, by Raquel de Queiroz, Balão cativo, Chão de Ferro, by Pedro Nava, Solo de Clarineta, by Erico Verissimo, and 51 poems bunched in the series "Primeiro Colégio" and "Fria Friburgo" in Boitempo II, by Carlos Drummond de Andrade. This gathering allowed the analysis of ideological and aesthetic aspects of texts and their relationship with a remarkable way of teaching the history of Brazilian education. For both, the theoretical framework used was the Critical Theory, particularly the texts produced by Marcuse, Adorno, Benjamin, in which questions are presented as critical paralysis, erudition, impoverishment of experience, negative indicators that only education can take to put autonomy and critical awareness as fundamental principles in the training of individuals. The investigation has found that the speeches of selected authors and their protagonists narrators